OPTIMALISASI KEUNTUNGAN PRODUKSI MAKANAN MELALUI PEMROGRAMAN LINEAR MENGGUNAKAN METODE SIMPLEKS (STUDI KASUS WARKOP PANCONG LUMER) - Abi Maulana Sugiartono; Achmad Mahardika Dwi Anda Putra Prasetio, Ammar Wildan, Paduloh (ADISAM PUBLISHER, 2024)
The aim of this research is to explore the role and contribution of Micro, Small and Medium Enterprises (MSMEs) in developing the Indonesian economy, as well as to apply it through linear programming using the simplex method in optimizing food production profits in the case study of Warkop Pancong Lumer. The main focus is overcoming challenges in managing cost of goods sold and calculating profits. Data was collected through observation and interviews with the owner and head of production. Analysis was carried out on the calculation of the cost of goods sold for Warkop Pancong Lumer to determine the effectiveness of applying the Simplex Method. This method succeeded in increasing profits according to the targets expected by Warkop Pancong Lumer. Apart from that, Warkop Pancong Lumer is also able to control the cost of goods sold more efficiently. This research is expected to provide significant benefits for actors, developers and researchers in the MSME sector in Indonesia. With the final calculation using the simplex method manually and using QM for Windows, Warkop Pancong Lumer succeeded in achieving a maximum profit of Rp. 260,000 daily is the result of careful analysis and precise calculations.